Patai's Chemistry of Functional Groups 2014
DOI: 10.1002/9780470682531.pat0874
|View full text |Cite
|
Sign up to set email alerts
|

Peroxide intermediates of oxidation processes: Organic trioxides

Abstract: The review discusses the results of studies on the chemistry of organic trioxides ROOOR (R = H or an organic radical) carried out in the past years. The spectral identification, structure, thermal stability and chemical properties of HOOOH, HOOO ⋅ , hydrotrioxides, open‐chain and cyclic trioxides (including fullerene ozonides) are described. The significance of trioxides for biochemistry, environmental chemistry, and organic synthesis is much higher than it was believed previously. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 282 publications
(249 reference statements)
0
5
0
Order By: Relevance
“…In separate experiments at ambient pressure and −20 to −10 °C, we confirmed that at the ozone/dioxygen fractions used in our work, either a neat substrate (2-butanol or butanone) or a mixture of these substrates in CCl 4 can be oxidized; 2-butanol to butanone; and butanone to acids, 3-hydroxybutanone, and 2,3-butanedione. Given that high concentrations of both tert -butyl hydroperoxide and ozone mutually promote their decomposition possibly by forming excess free radicals, , we infer that hydroperoxide may not form in significant amounts at the conditions used in our work where high ozone utilization is observed. As for 3-hydroxybutanone and 2,3-butanedione as oxidation products from butanone, they form in significant amounts only at relatively high concentrations of either 2-butanol or butanone.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…In separate experiments at ambient pressure and −20 to −10 °C, we confirmed that at the ozone/dioxygen fractions used in our work, either a neat substrate (2-butanol or butanone) or a mixture of these substrates in CCl 4 can be oxidized; 2-butanol to butanone; and butanone to acids, 3-hydroxybutanone, and 2,3-butanedione. Given that high concentrations of both tert -butyl hydroperoxide and ozone mutually promote their decomposition possibly by forming excess free radicals, , we infer that hydroperoxide may not form in significant amounts at the conditions used in our work where high ozone utilization is observed. As for 3-hydroxybutanone and 2,3-butanedione as oxidation products from butanone, they form in significant amounts only at relatively high concentrations of either 2-butanol or butanone.…”
Section: Resultsmentioning
confidence: 95%
“…Further, peroxides cannot possibly activate butanols and butanes without a catalyst at ambient temperature. Therefore, trioxides are more likely involved, although, at ambient temperature, they are probably too unstable , to observe by 1 H NMR spectroscopy …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A ZW intermediate has a chain of three covalently bound electronegative atoms, being a far-off analog of trioxides ROOOR . These compounds are easily decomposed along the peroxide bond, and ZW may undergo a similar transformation.…”
Section: Resultsmentioning
confidence: 99%
“…A ZW intermediate has a chain of three covalently bound electronegative atoms, being a far-off analog of trioxides ROOOR. 46 These compounds are easily decomposed along the peroxide bond, and ZW may undergo a similar transformation. The activation energies of this TS11 process are rather small (Table 4); moreover, TS11 energy is decreased in the solvent.…”
Section: Key Structures and Reagents' Interaction Energymentioning
confidence: 99%